Phosphotyrosine-dependent in vitro reconstitution of recombinant LAT-nucleated multiprotein signalling complexes on liposomes. - Sangani, D; Venien-Bryan, C; Harder, T (2009)
Numerous cell surface receptors propagate activation signals to the interior of the cell via tyrosine phosphorylation of transmembrane proteins. This leads to the phosphotyrosine (PiY)-mediated recruitment of cytoplasmic signalling protein complexes which catalyze crucial biochemical signalling reactions. Here we describe the first in vitro reconstitution of such PiY-nucleated protein complexes on an artificial lipid membrane. A tyrosine phosphorylated recombinant variant of the transmembrane adaptor protein Linker for Activation of T cells (PiYLAT) was anchored in liposomes. These PiYLAT proteoliposomes specifically recruited cooperative high avidity signalling protein complexes from Jurkat cytosol. Nucleation of signalling protein assemblies readily occurred on PiYLAT liposomes composed of phosphatidylserine, but not on PiYLAT liposomes composed of phosphatidylcholine. Purified recombinant grb2 alone did not stably associate with tyrosine phosphorylated LAT proteoliposomes. However, when grb2 was presented to the PiYLAT proteoliposomes in the context of Jurkat cytosol it was incorporated into multiprotein signalling complexes. Together the data suggest that these reconstituted high-avidity signalling protein complexes represent a cooperative protein network. This novel in vitro approach offers a novel technology permitting biochemical, structural, and pharmacological analyses of plasma membrane receptor signalling complexes.